2005
DOI: 10.1007/s00011-005-1363-8
|View full text |Cite
|
Sign up to set email alerts
|

Intercellular adhesion molecule-1 (ICAM-1) in ulcerative colitis: Presence, visualization, and significance

Abstract: The intensive research of recent years has suggested that the cause of ulcerative colitis (UC) involves a genetic predisposition to an uncontrolled or unbalanced immune response to luminal or epithelial antigens or against other external factors. Intercellular adhesion molecule-1 (ICAM-1) is pivotal for the influx of neutrophil granulocytes into colonic mucosa, and gene analyses have found polymorphisms in the gene encoding ICAM-1, indicating that changes in ICAM-1 function may be involved in the pathogenesis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 123 publications
1
28
0
3
Order By: Relevance
“…In antigen presenting cells including macrophages, ICAM-1 participates in cell-cell interactions during antigen presentation while in other cell types ICAM-1 functions in microbial pathogenesis and as a signal transduction molecule. 25,26 Physiologically, ICAM-1 is expressed at a low basal level, 27 however during inflammatory and immune responses, ICAM-1 level increased substantially and aberrantly at sites of inflammation contributing to a number of inflammation-related diseases and injuries such as endotoxin-induced airway disease 28,29 and asthma, 27,30 arthritis, 31 ulcerative colitis 32 and chronic cholangiopathies. 21 In cancer, ICAM-1 has been mainly implicated in local inflammatory tumor microenvironment, 33 tumor progression and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…In antigen presenting cells including macrophages, ICAM-1 participates in cell-cell interactions during antigen presentation while in other cell types ICAM-1 functions in microbial pathogenesis and as a signal transduction molecule. 25,26 Physiologically, ICAM-1 is expressed at a low basal level, 27 however during inflammatory and immune responses, ICAM-1 level increased substantially and aberrantly at sites of inflammation contributing to a number of inflammation-related diseases and injuries such as endotoxin-induced airway disease 28,29 and asthma, 27,30 arthritis, 31 ulcerative colitis 32 and chronic cholangiopathies. 21 In cancer, ICAM-1 has been mainly implicated in local inflammatory tumor microenvironment, 33 tumor progression and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in this region may also affect the binding of ICAM-1 to ligands such as the lymphocyte function-associated antigen-1 (LFA-1) and the complement receptor 3 (CR3) [25,26]. These alterations in ICAM-1-ligand combinations have been reported to enhance the adhesion of leukocytes to vascular endothelial cells and facilitate their infiltration into mucosa [5,27]. ICAM-1 has been widely studied in recent years, and several recent studies have suggested that the ICAM-1 K469E gene polymorphism is associated with IBD susceptibility.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple lines of evidence have suggested that changes in ICAM-1 expression and function might be involved in the pathogenesis of UC and CD [5,6]. In addition, clinical trials of Alicaforsen, an antisense oligonucleotide that inhibits the synthesis of ICAM-1, have shown positive results in the treatment of patients with UC [7].…”
Section: Introductionmentioning
confidence: 99%
“…Now we know that the presence of pro-inflammatory markers in blood may be in part responsible for degenerative diseases, characteristic of aging and reposing on accelerated cell senescence. Through their clinical relevance, inflammatory markers can witness, via endothelial dysfunction, their implication in the occurring of disease (Edelman, 1993;Vanier, 2005;Farhadi et al, 2003;Garcìa-Cardena & Gimbrone, 2006;Ingber, 2003;Marconi et al, 2003).…”
Section: Anti-inflammation To Decrease Cell Senescencementioning
confidence: 99%